29.8k views
1 vote
Decide!!!!!!!!!!!!!!!!!!!

Decide!!!!!!!!!!!!!!!!!!!-example-1

1 Answer

6 votes

Answer:

  • n = {9, 10}

Explanation:

Let the equation be:

  • n² - 19n + 91 = k²

Multiply both sides by 4 and complete the square:

  • 4n² - 76n + 364 = 4k²
  • (2n)² - 2(2n)(19) + 19² + 3 = 4k²
  • (2n - 19)² - 4k² = - 3
  • (2n + 2k - 19)(2n - 2k - 19) = -3

Since -3 = 1(-3) = (-1)*3, we have following options:

1)

  • 2n + 2k - 19 = 1
  • 2n - 2k - 19 = -3

Eliminate k by adding up equations:

  • 4n - 38 = -2
  • 4n = 36
  • n = 9

2)

  • 2n + 2k - 19 = -1
  • 2n - 2k - 19 = 3

Eliminate k by adding up equations:

  • 4n - 38 = 2
  • 4n = 40
  • n = 10
User Kyrbi
by
5.6k points